Copolymers comprising monomers with various dipole and quadrupole as active material in organic field effect transistors - Singh, Saumya; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam (Journal of Physical Chemistry C, 2016)
Copolymers of 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) and diketopyrrolopyrrole (DPP) were synthesized. The BODIPY has a permanent dipole and the DPP has a quadrupole. The dipole and the quadrupole in the monomers are expected to bring the polymers closer and to improve the charge-transport properties. By judicious choice of these monomers, the electron wave function is evenly distributed through the molecules. However, we notice that the torsional angle at the connecting point of BODIPY and DPP is a function of the methyl moieties at the beta,beta' position of the BODIPY. We found that the polymer comprising DPP and BODIPY without methyl moiety at beta,beta' position showed a torsional angle of 27, the lowest among the three polymers studied in this work. The absorption spectrum of the polymer showed transitions because of vibronic coupling indicating linearity along the polymer backbone. The band gap of the polymer was found to be 1.2 eV. The thermally stable polymer showed an ambipolar charge transport of 0.01 cm(2)/(V s).